2021
DOI: 10.13031/trans.13877
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Cotton Growth and Yield Response to Irrigation Practices for Thermally Limited Growing Seasons in Kansas

Abstract: HighlightsLater planting and greater site elevation or latitude decreased seasonal growing degree days and cotton yield in Kansas.Higher irrigation capacity (rate) usually increased lint yield, which was probably due to increased early boll load.Strategies for splitting land allocations between high irrigation rates and dryland did not increase production.Cotton may reduce irrigation withdrawals from the Ogallala aquifer, but the Kansas growing season limits production.Abstract. Precipitation in the western Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…The model lint yield uncertainty under both dryland and irrigated conditions was validated for the Texas High Plains and in southwest Kansas, which indicated agreement between limited observed and modeled trials [10,31]. The 2006 to 2012 mean lint yields of multiple cultivars grown southwest of Garden City, near Hugoton, were regressed on the GOSSYM modeled cotton lint yield of one common variety file with good agreement, R 2 = 0.93, [10]. Observed higher, 1600-1800 kg ha −1 , yield levels were underestimated 10-20% by GOSSYM, possibly because the specified N fertility level was insufficient above 1200 kg ha −1 .…”
Section: Cotton Growth Model and Site Characteristicsmentioning
confidence: 77%
See 2 more Smart Citations
“…The model lint yield uncertainty under both dryland and irrigated conditions was validated for the Texas High Plains and in southwest Kansas, which indicated agreement between limited observed and modeled trials [10,31]. The 2006 to 2012 mean lint yields of multiple cultivars grown southwest of Garden City, near Hugoton, were regressed on the GOSSYM modeled cotton lint yield of one common variety file with good agreement, R 2 = 0.93, [10]. Observed higher, 1600-1800 kg ha −1 , yield levels were underestimated 10-20% by GOSSYM, possibly because the specified N fertility level was insufficient above 1200 kg ha −1 .…”
Section: Cotton Growth Model and Site Characteristicsmentioning
confidence: 77%
“…Model uncertainty for plant height, leaf area index, and simulated water use was previously validated under semiarid conditions that showed calculated ET values were within 10% of measured use [30]. The model lint yield uncertainty under both dryland and irrigated conditions was validated for the Texas High Plains and in southwest Kansas, which indicated agreement between limited observed and modeled trials [10,31]. The 2006 to 2012 mean lint yields of multiple cultivars grown southwest of Garden City, near Hugoton, were regressed on the GOSSYM modeled cotton lint yield of one common variety file with good agreement, R 2 = 0.93, [10].…”
Section: Cotton Growth Model and Site Characteristicsmentioning
confidence: 88%
See 1 more Smart Citation
“…Similarly, Himanshu et al [47] found that imposing water deficits in the initial or final growth stages had little effect on seed cotton yield, while the peak bloom growth stage (GS4) was the most sensitive stage to water stress. While cotton has not been a common crop in western Kansas, it has the potential to produce net returns comparable to corn, and Baumhardt et al [48] found that short season, early planted cotton could be a viable, low-water requirement crop in the southwestern part of Kansas.…”
Section: Innovations In Managementmentioning
confidence: 99%
“…Cotton requires less irrigation than corn and thus has become an irrigated crop of interest in western Kansas despite the limited thermal units available for production. Modeling was used to examine the effects of crop emergence date, irrigation capacity, and irrigation application period on cotton production in three western Kansas locations (Baumhardt et al, 2020). Earlier emergence generally increased yield and water productivity.…”
Section: Irrigation Management (Strategies Scheduling and Modeling)mentioning
confidence: 99%